Impact of maxillofacial surgery on patient’s quality of life and psychological well-being - Abdulfattah Sindy, Ebtihal; Alkhowaiter, Fawaz Abdulrahman; Alzahrani, Matar Abdulrahman; Alotaibi, Turki Nasser; Alqahtani, Salem Ali; Alameer, Mohammed Ghazi; Al Shaikh, Mohammed Abdullaziz; Allah Alanazi, Faisal Dhaif; Jafar, Samih Mohammed; Alotaibi, May Mansour (International Journal Of Community Medicine And Public Health, 2024)
Maxillofacial surgery has a transformative impact on patients, addressing both physical impairments and psychological challenges. Conditions such as trauma, congenital anomalies, and deformities often result in functional limitations and social stigma, significantly affecting quality of life. Through corrective procedures, patients experience improvements in essential functions, including mastication, speech, and respiration, which contribute to better overall health and autonomy. Advancements in surgical technology, such as computer-aided design, virtual surgical planning, and custom implants, have enabled precise and patient-specific interventions, further enhancing functional outcomes. The psychological benefits of maxillofacial surgery are equally profound, as the restoration of facial aesthetics fosters improved self-esteem, reduced social anxiety, and enhanced emotional resilience. Patients often regain confidence to engage in personal and professional interactions, overcoming societal prejudices linked to visible deformities. These outcomes underscore the interdependence of physical recovery and mental well-being in the context of surgical interventions. Social reintegration plays a pivotal role in the recovery process, with patients reporting renewed participation in social activities and strengthened relationships. Satisfaction with surgical outcomes is closely tied to both aesthetic and functional success, reflecting the importance of managing patient expectations through preoperative planning and counseling. Integration of psychological support within the surgical care pathway further amplifies these benefits, ensuring a holistic approach to patient well-being. By addressing physical, psychological, and social dimensions, maxillofacial surgery demonstrates its potential to transform lives. The integration of innovative technologies and interdisciplinary care continues to enhance patient outcomes, emphasizing the need for comprehensive strategies that address both the external and internal challenges faced by individuals with maxillofacial conditions. These advancements highlight the vital role of maxillofacial surgery in improving quality of life and fostering long-term patient satisfaction.